Financing of small and medium scale enterprises and its growth impact in Nigeria - Charles Onyeiwu; Obumneke Bob Muoneke; Udo Nkoyo (The Journal of Entrepreneurial Finance (JEF), 2020)
We examined the extent to which SMEs financing influenced economic growth in Nigeria through the use of time-series data from 1999-2018. After a literature search, other factors possessing the potential to influence the dependent variable ASGDP was added to the research model. Relying on Ordinary Least Squares estimation using E-views 10.0, findings shows that lending rate reduces ASGDP by 7% and gross capital formation reduces ASGDP by 5%. On the other hand, surprisingly, credit to SMEs did not retain the massive effect on growth as seen in previous studies. We can attribute this to our choice of adopting SME contribution to GDP as our target variable. Electricity distribution increased ASGDP by 4.6%. Policy recommendations to the Federal Government and the apex bank are; capital inflows vis-à-vis affordable local loans to SMEs at single digit (interest rate) is necessary to enhance the performance of SMEs and growth simultaneously. Electricity tariffs should be heavily subsidized for small and medium scale enterprises to decrease their overhead cost.
Keywords: G21; G32; L26; M13; O4; M1; M13; 650; Commercial banks; SMEs financing; Electricity distribution; economicgrowth; Nigeria